The influence of herbivores on primary producers can vary spatially and interact with disturbance. Issue 9 (23rd February 2016) - Carnell, Paul E.; Keough, Michael J.
Abstract : Identifying the major drivers of ecosystem change remains a central area of ecological research. Although top–down drivers of change have received particular focus, we still have little understanding of how consistently these factors control an ecosystem's shift in both directions, between different ecosystem states. Using a crossed experiment in a shallow embayment in southeastern Australia, we investigated the roles of disturbance (kelp removal) and sea urchin herbivory (via increased density) to determine their contributions to shifts away from a kelp‐dominated community. In a second experiment, done in urchin barren areas at two sites, we tested whether reductions in ambient sea urchin densities allowed an algal shift in the reverse direction. In both experiments, we observed that high densities of sea urchins could negatively influence kelp and macroalgal abundance. However, in the kelp bed, a moderate or severe disturbance resulted in a comparable algal response, irrespective of urchin density. The influence of sea urchins also varied dramatically between the two urchin barren sites. Here, reducing urchin densities resulted in algal recovery at one site, but at the other site, substantial colonisation of barren areas by canopy‐forming brown algae and Ulvales occurred across all (low, medium, and high) urchin density treatments. Our findings illustrate multiple pathways of urchin barren creation and algal recovery, and reveal that shifts both to and from an urchin barren state can occur irrespective of herbivore pressure. These alternate pathways can operate over short spatial distances or with different regimes of disturbance.